2011
DOI: 10.1186/1471-2458-11-749
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of Aboriginal health promotion from an ecological perspective

Abstract: BackgroundFor health promotion to be effective in Aboriginal and Torres Strait Islander Communities, interventions (and their evaluation) need to work within a complex social environment and respect Indigenous knowledge, culture and social systems. At present, there is a lack of culturally appropriate evaluation methods available to practitioners that are capable of capturing this complexity. As an initial response to this problem, we used two non-invasive methods to evaluate a community-directed health promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…Changes in food supply were achieved through targeting remote stores [16,22,23,26,27,28,50], canteens at schools [16,26] and a sporting club [44], the last incorporating the ā€œFruit Shareā€ program that provided fruit for club members on training nights. These activities were supported by staff development through health promotion training [44], and support from local councils in the form of air charters [23] and provision of office space for project workers [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in food supply were achieved through targeting remote stores [16,22,23,26,27,28,50], canteens at schools [16,26] and a sporting club [44], the last incorporating the ā€œFruit Shareā€ program that provided fruit for club members on training nights. These activities were supported by staff development through health promotion training [44], and support from local councils in the form of air charters [23] and provision of office space for project workers [26].…”
Section: Resultsmentioning
confidence: 99%
“…Changes in food supply were achieved through targeting remote stores [16,22,23,26,27,28,50], canteens at schools [16,26] and a sporting club [44], the last incorporating the ā€œFruit Shareā€ program that provided fruit for club members on training nights. These activities were supported by staff development through health promotion training [44], and support from local councils in the form of air charters [23] and provision of office space for project workers [26]. Breakfast programs for children were reported [26,44], as was education through school curriculum change [26], the engagement of Elders [23], and other education strategies such as ā€œshelf talkersā€ and store tours to aid community membersā€™ recognition of target foods [23,26,28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rumbalara Football Netball Club stands out by focussing on promoting healthy lifestyles and preventative health programs rather than crisis intervention services [4]. All three ACCOs identified that their programs were not being evaluated and reported in ways that reflect how they address social determinants of First Peoplesā€™ health and the holistic nature of their design [5]. This is not unique to this region or country [6ā€“8].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously used an ecological model as an indicator of health program complexity and design [5, 9] and found it to have value for this purpose, despite certain limitations [10]. In theory, health programs are more likely to be effective if they act to change the environment in which people live as well as working with individuals.…”
Section: Introductionmentioning
confidence: 99%